2014
DOI: 10.2190/ag.78.3.c
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Time Estimation in Older Adults

Abstract: The ability to correctly estimate time is important for many daily activities, such as cooking and driving. This study investigated the stability time estimation in healthy older adults and compared them to healthy younger adults. Participants were tested and retested across the duration of 1 year. Using a prospective paradigm, verbal estimates were provided for intervals of 10, 25, 45, and 60 seconds. Although the older adults demonstrated a greater magnitude of error in their time estimates than younger adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In a verbal estimation task, Rueda and Schmitter‐Edgecombe showed that all participants on average underestimated the intervals but the absolute error of the older participants was larger than that of younger participants (see also Ref. ). These results suggest that the different findings between studies could be due to the varying task complexity and that under higher cognitive load, findings tend to support the predictions of slower clock speed or less efficient integration of clock signals due to lower attentional resources …”
Section: Temporal Processing Of Healthy Agingmentioning
confidence: 96%
“…In a verbal estimation task, Rueda and Schmitter‐Edgecombe showed that all participants on average underestimated the intervals but the absolute error of the older participants was larger than that of younger participants (see also Ref. ). These results suggest that the different findings between studies could be due to the varying task complexity and that under higher cognitive load, findings tend to support the predictions of slower clock speed or less efficient integration of clock signals due to lower attentional resources …”
Section: Temporal Processing Of Healthy Agingmentioning
confidence: 96%
“…Time production tasks can serve as effective tools in evaluating these individual differences in clock speed and/or the storage of the clock reading into memory [ 28 , 29 ]. The rate of functioning of the internal clock may be associated with one’s preferred spontaneous motor tempo and may also be modulated by working memory resources [ 8 , 22 , 30 , 31 ]. The pulse emission rate can be manipulated by a number of factors, including resource allocation, pharmacological agents, brain lesions, and click training [ 8 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…While interval perception has been examined in various populations, such as young healthy adults, children (e.g., Clement and Droit-Volet, 2006 ; Droit-Volet and Rattat, 2007 ; Rattat and Droit-Volet, 2007 ; Droit-Volet, 2008 , 2017 ; Droit-Volet and Izaute, 2009 ; but see Droit-Volet et al, 2007 , for short-term memory of single interval), older adults (e.g., McCormack et al, 1999 , 2002 ; Lustig and Meck, 2001 ; Bherer et al, 2007 ; Lustig and Meck, 2011 ; Anderson et al, 2014 ), and clinical patients (e.g., mild cognitive impairment: Rueda and Schmitter-Edgecombe, 2009 ; Heinik, 2012 ; Mioni et al, 2018 ; Alzheimer’s disease: Nichelli et al, 1993 ; Hellstrom and Almkvist, 1997 ; Carrasco et al, 2000 ; Caselli et al, 2009 ; El Haj et al, 2013 , 2014 ), the working memory aspects of multiple intervals have been left uninvestigated. When it applies to real life situations, working memory always takes place in our timing and time perception.…”
Section: Discussionmentioning
confidence: 99%